Characteristics of the naturalized flora of Southern Africa largely reflect the non‐random introduction of alien species for cultivation. Issue 12 (12th October 2021) - Omer, Ali; Fristoe, Trevor; Yang, Qiang; Maurel, Noëlie; Weigelt, Patrick; Kreft, Holger; Bleilevens, Jonas; Dawson, Wayne; Essl, Franz; Pergl, Jan; Pyšek, Petr; van Kleunen, Mark
Abstract : Biological invasions are one of the most defining features of the Anthropocene. Most studies on biological invasions focus on the later stages of the invasion process, that is after species have already become naturalized. It is frequently overlooked, however, that patterns in origin, phylogeny and traits of naturalized alien species might largely reflect which species have been introduced in the first place. Here, we quantify and assess such introduction biases by analyzing 5317 plant species introduced for cultivation (i.e. primarily as ornamental garden plants) in the 10 countries composing Southern Africa. We show that this cultivated alien flora represents a non‐random subset of the global flora and that this bias at the introduction stage largely contributes to patterns in geographic origin, phylogenetic composition and traits of the naturalized flora. For example, while species from Australasia are, compared to the global flora, disproportionally overrepresented in the naturalized cultivated flora of Southern Africa, this pattern is driven by their higher likelihood of introduction for cultivation. The same is true for the overrepresentation of free‐standing woody species in the naturalized cultivated flora. The strong phylogenetic clustering of the naturalized cultivated flora is also, to a large extent, driven by introduction bias. Although functional traits explained little variation in naturalization success of cultivated plants, naturalization success was more likely for plants with intermediate seed mass and height and high specific leaf area. Thus, despite strong biases in which species have been introduced to Southern Africa, there are significant patterns in the species characteristics related to naturalization probability. Our quantification of introduction biases demonstrates that they are huge, and that accounting for it is important to avoid over‐ or under‐emphasizing the characteristics of successfully naturalized alien plants.